INDONESIAN PRE-SERVICE ENGLISH TEACHERS’ EXPERIENCES OF TEACHING PRACTICUM DURING THE COVID-19 PANDEMIC AND THEIR TEACHER IDENTITY CONSTRUCTION - Endang Ekawati; Elih Sutisna Yanto; Abdul Kodir Al-Baekani (PROJECT (Professional Journal of English Education), 2022)
Pre-service English teachers' identity construction as a teacher is complicated and influenced by several factors. The current study intends to investigate how Indonesian pre-service English teachers construct their teacher identities when performing the teaching practicum during the COVID-19 pandemic. The study employed a narrative inquiry to investigate pre-service teachers' experiences and how they interpreted those experiences. To collect data from the participants, the authors used semi-structured interviews and their narrative frames.. Additionally, this study used documentation, such as lesson plans and teaching practicum reports to enrich and reinforce the data. Finally, the result of the collected data was analyzed using thematic analysis. The findings showed that pre-service English teachers encountered several constraints when completing a teaching practicum during the COVID-19 pandemic that could have limited how they constructed their teacher identities. Constrained factors include government rules that enforced teaching-learning activities during the pandemic and unsupportive school mentors. However, some participants also have supportive school mentors who guide them as they learn how to teach. This research demonstrates the crucial role that school mentors play in constructing pre-service teachers' identities. Furthermore, pre-service teachers overcame the difficulties of their teaching during the COVID-19 pandemic by using their creativity and resilience. Keywords:  Pre-Service English Teachers, Teacher Identity, Narrative Inquiry, COVID-19 Pandemic